Nikki Webster. ([Australia] : Nikki Webster, 2012)
Official website of singer Nikki Webster who was introduced to the world with her performances at the opening and closing cermonies of the Sydney 2000 Olympic Games.
Title from title screen (viewed on 18 January 2016)
Mode of access: Available online. Address as at 21/01/2016
Selected for archiving
Keywords: Webster, Nikki; Popular music -- 2000-; Women singers -- Australia; Australian